Health psychology : theory, research, and practice - Marks, David (David F.) (Los Angeles, Calif. : SAGE, 2011)
This textbook has been thoroughly updated and revised to make it even more essential for course teaching. Retaining the celebrated approach of previous editions in examining critical perspectives in health psychology, the book incorporates research from a fuller range of perspectives including more 'mainstream' health psychology.
Health psychology in context -- Health psychology: an introduction -- Macro-social environment and health -- Social inequalities, social justice and health -- Culture and health -- A-Z of research methods in health psychology -- Health behaviour and experience -- Theories, models and interventions applied to sexual health -- Food, eating and environment -- Alcohol and drinking -- Tobacco and smoking -- Physical activity and exercise -- Health promotion and disease prevention -- Information and communication -- Stress and coping -- Screening and immunization -- Health literacy -- Community approaches within health psychology -- Illness experience and health care -- Lay representations of illness -- Illness and personality -- Medicine taking: adherence and resistance -- Pain -- Cancer and chronic diseases.
Includes bibliographical references (p. [515]-568) and indexes.
Keywords: Clinical health psychology; Behavioral Medicine -- methods; Health Behavior; Health Promotion; Preventive Medicine; Risk Factors; Health behavior; Health promotion; Preventive medicine; Risk factors